2021
DOI: 10.21608/jfds.2021.167053
|View full text |Cite
|
Sign up to set email alerts
|

Use of Banana Peel As A By-Product to Increase The Nutritive Value of The Cake

Abstract: The aim of this study was to demonstrate the nutritional value of banana peel powder (BPP) by highlighting its antimicrobial and antioxidant material. Additionally, to use the (BPP) as a low-cost substitute for wheat flour in a cake. Additionally, the findings of BPP at various concentrations (3,6,9,12, and 15%) were compared to some critical quality properties such as physical, chemical, and microbial properties, as well as the sensory characteristics of cake. The present findings indicate that more than 50.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 39 publications
1
15
1
Order By: Relevance
“…(2020) Musa cavendish , Ripe 13.08 (0.09) 6.9 12.55 (0.06) 57.74 9.73 (0.56) Gómez-Montaño et al. (2019) Musa cavendish , Ripe 10.03 (0.17) 25.19 (0.12) 15.10 (0.19) 7.04 (0.08) 44.64 (0.19) - Ahmed et al. (2021) – Not reported.…”
Section: Resultsmentioning
confidence: 99%
“…(2020) Musa cavendish , Ripe 13.08 (0.09) 6.9 12.55 (0.06) 57.74 9.73 (0.56) Gómez-Montaño et al. (2019) Musa cavendish , Ripe 10.03 (0.17) 25.19 (0.12) 15.10 (0.19) 7.04 (0.08) 44.64 (0.19) - Ahmed et al. (2021) – Not reported.…”
Section: Resultsmentioning
confidence: 99%
“…Cookies are considered the leading group among snack food products in most parts of the world . The traditional preparation of cookies is easy and simple, and the basic ingredients that are usually added in the preparation of cookies are flour, eggs, sugar, and butter . Based on the method of preparation, cookies are classified as drop, pressed, molded, rolled, refrigerated, and bar.…”
Section: Introductionmentioning
confidence: 99%
“…Banana peel is rich in fiber, antioxidants, vitamin antioxidants, vitamin B6, vitamin C, magnesium, and potassium and is destitute in terms of sugars, fats, calories, and cholesterol. , Therefore, it can be fairly utilized as an additive to enhance the quality, shelf life, and nutritional value of food products, such as cookies. In this regard, studies have indicated that banana peel could be a potential source of antioxidants and nutritional enhancements in the food industry. ,,,, Balakrishnan studied the effect of banana peel extract in cake formulation to enhance color and bioactive properties and reported that the banana peel extract is a good source of natural food color with a positive effect on nutrients. Additionally, the banana peel extract promotes human health and also extends the shelf life of the products as it is an antioxidant and antimicrobial natural source.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations